African Ethical Aesthetics and the Christian Life: A Study in Theological and Moral Similitude - Bolarinwa, Adebayo Oluwasegun; Alaka-Osinowo, Bolayemi Sarah (Interdisciplinary Journal Of Lifelong Learning, 2025)
Ethics form the foundational identity of every society, shaping its internal cohesion and external perception. In traditional African societies, ethical life is not individualistic but communal, marked by values such as solidarity, mutual care, and collective responsibility. These values are expressed not only as moral obligations but also as aesthetic ideals—harmonious living that reflects the beauty of ordered community life. This paper examines how African ethical aesthetics, particularly the communal ethos, can serve as a constructive framework for reimagining Christian moral life in contemporary contexts. Drawing on theological reflection and ethical theory, the study argues that African communal ethics align closely with biblical teachings on love, unity, and mutual edification within the body of Christ. In light of increasing individualism, rivalry, and power struggles within modern Christian communities, the paper suggests that retrieving and integrating African communal ethics can revitalize the lived expression of Christian faith. By positioning African ethics not merely as cultural heritage but as a theological resource, the study calls for a renewed emphasis on brotherhood, shared responsibility, and spiritual solidarity in the Church. Ultimately, it concludes that the aesthetic vision of African ethics provides a compelling similitude for the Christian life—where moral beauty is found in community, not competition.